Infarto agudo al miocardio secundario al uso de cocaína. Caso clínico y revisión del tema - Ugalde P., Héctor; Ramírez N., Alfredo (Revista Hospital Clínico Universidad de Chile, 2008)
There is same evidence to suggest that the use of cocaine has increased in our country in recent years. The negative actions of the drug can be observed in different organs; the cardiovascular system is particularly vulnerable. We present the clinical case of a young man who, as a consequence of occasional inhalation of cocaine presents an acute myocardial infarction. The reperfusion of the coronary artery was obtained with a Coronary angioplasty very close to the beginning of the occlusion. We discuss the pathophysiology of this particular form of myocardial infarction and emphasis the different therapeutic options in this arena and in particular, our preferred way of treatment